ANALISIS KEBIJAKAN HUTANG, DIVIDEN DAN NILAI PERUSAHAAN SEBAGAI MEKANISME CORPORATE GOVERNANCE PADA PERUSAHAAN JAKARTA ISLAMIC INDEX (JII) DAN INDUSTRI PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA - Prihandini, Wiwiek (MAJALAH ILMIAH WIDYA, 2012)
Conflicts of interest between owners and managers arise because managers do not always act in the interest of the owner. Debt and dividend policy is a management tool that can be used to reduce conflict. This study aimed to identify the effect of debt and dividend policy to the value of the company as a corporate governance mechanism, and the difference between group companies which are included in the Jakarta Islamic Index (JII) by the banking industry listed on the Indonesia Stock Exchange. This study used data of 2009 Financial Statements Â processed using multiple regressions. Debt policy and dividend policy of each are proxies by Debt Equity Ratio and Cash Dividend. The conclusion of this study that dividend policy affects firm value, and there was no significant difference between companies that fall into the category JII with companies in the banking group on the effect of debt policy and dividend policy on firm value.